Protestant-Catholic relations in America : World War I through Vatican II - Curry, Lerond (Lexington : University Press of Kentucky, 2015)
The first general survey of relations between Protestants and Catholics in America during the past half century will be welcomed not only by social historians but by clergymen and laymen interested in the development of constructive interfaith relations. Lerond Curry has traced the major trends in this fifty-year period and analyzed the underlying factors that influenced them. Much of his account is based on correspondence and personal interviews with people who took part in the events and movements he describes. The rapid growth of Catholic population just before World War I, along with increas.
Cover; Title; Copyright; Contents; Preface; I. Protestant Adjustment to Catholic Growth: 1917-1939; II. Catholicism in America Comes of Age: 1939-1955; III. Toward Relationships of Maturity: 1955-1967; Appendix A. Excerpts from Papal Documents Concerning Non-Catholic Christian Bodies; Appendix B. Excerpts from United States Supreme Court Decisions on Matters Related to Parochial Schools; Notes; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; R; S; T; U; V; W; Y.
Includes bibliographical references and index.
Print version record.
Keywords: Protestant churches -- Relations -- Catholic Church; Catholic Church -- Relations -- Protestant churches; United States -- Religion; Catholic Church -- Relations -- Protestant churches; Protestant churches -- Relations -- Catholic Church; United States -- Religion; RELIGION / Christian Theology / Ecclesiology; Electronic books